Whole-body MRI in patients with non-bacterial osteitis: radiological findings and correlation with clinical data - Arnoldi, Andreas Paul; Schlett, Christopher L.; Weckbach, Sabine (European radiology, 2017)
OBJECTIVES: To correlate clinical findings of Non-bacterial Osteitis (NBO) with whole-body MRI (WB-MRI) findings and determine a radiologic index for NBO (RINBO) which allows standardized reporting of WB-MRI. METHODS AND MATERIALS: In a prospective study, 40 patients with diagnosis of NBO underwent clinical examination and WB-MRI in which STIR- and T1- weighted images were assessed for NBO-typical lesions. Parameters of interest for RINBO were: number of radiologically active lesions (RAL), size of the patients' maximum RAL presence of extramedullary and spinal involvement. Results were tested for statistical agreement of clinical and MR-based lesion detection. RINBO was tested for correlation with clinical activity. RESULTS: 62/95 clinically/radiologically active lesions were found in 30/33 patients. In 45 % of the cohort, more active lesions were detected by WB-MRI than by clinical examination. RINBO was a significant predictor for the presence of clinically active lesions. CONCLUSION: WB-MRI is a powerful diagnostic tool for patients with NBO which can reveal asymptomatic disease activity. With RINBO a standardized evaluation approach is proposed which helps assessing radiologic disease burden and predicts clinical disease activity. KEY POINTS: • Whole body MRI is a powerful diagnostic tool for patients with non-bacterial Osteitis. • Whole body MRI can reveal asymptomatic disease activity. • The radiologic index RINBO offers a standardized evaluation approach.